A scoping review on mapping the digital leadership constructs for educational settings: what we can learn? - Nurhafizah Abdul Musid; Mohd Effendi Ewan Mohd Matore; Aida Hanim A. Hamid (Institute of Advanced Engineering and Science, 2024)
Another style of leadership utilized in the field of education, notably digital leadership, has become more prevalent. Studies on digital leadership are receiving more attention, but there has not been much focus on scoping reviews. To determine the constructs of digital leadership, this study undertakes a scoping review. Accordingly, a scoping review on human-influenced and non-human-influenced constructs in measuring digital leadership was carried out in this study. This scoping review follows six processes: i) identification of the research question; ii) literature research; iii) selection of relevant studies; iv) charting the information; v) collating, summarizing, and reporting of study results; vi) discussion of the results and implications for future research. A scoping review was conducted via the Web of Science, Scopus, and Google databases to identify empirical studies on constructs in digital leadership since 2014. Next, the titles and abstracts for selected full-text articles were screened manually. Data from the included articles were charted and summarized. To develop specific and empirical data for measuring digital leadership, the study found that 22 constructs were influenced by humans and three constructs were non-human-influenced. Interpersonal and intrapersonal skills were separated from the constructs that were influenced by humans, with 15 constructs constituting intrapersonal skills and seven constructs constituting interpersonal skills. The results will help identify the crucial components of successful digital leadership. Future research is warranted in creating programs such as workshops, training, and conferences to promote digital leadership and further improve the study.